Pemberdayaan Komunitas Pesisir Melalui Diseminasi Inovasi Kerupuk Cumi Singkong untuk Pengembangan Ekonomi Berkelanjutan - Dinda Mardiani Lubis; Lizha Dwi Mulya Putri; Sudirman Adibrata (PUSAKA ABDIMAS, 2025)
To address this issue, the program introduced squid–cassava crackers as a downstreaming initiative that integrates local resources while embodying the agromaritime concept. The main objective was to enhance community capacity in developing value-added processed products and to foster the growth of a creative economy based on local resources. The program was conducted through socialization, training, and practical demonstrations, involving 70 participants consisting of teachers, students of SMAN 1 Merawang, partner foundations, and local stakeholders. Participants were purposively selected to ensure the program’s relevance. Knowledge transfer was carried out through lectures, interactive discussions, and hands-on product-making sessions, complemented by the provision of a grating machine to support program sustainability. The results indicated a significant improvement in participants’ knowledge and interest in product downstreaming. The high level of enthusiasm, particularly during the cooking demonstration, highlighted the potential of squid–cassava crackers as a promising agromaritime innovation. This product successfully combines marine and terrestrial resources, creating new entrepreneurial opportunities and strengthening food security. In conclusion, this initiative demonstrates that disseminating squid–cassava cracker innovation can serve as an entry point for developing a creative economy in coastal areas.